A rare case of granulomatous Wegener with multiple pyoderma gangrenosum‐like ulcers. Issue 2 (17th February 2020) - Jorgaqi, Ekleva; Fida, Monika; Janushaj, Elmijola; Mala, Ritjana; Vasili, Ermira
Abstract: Wegener's granulomatosis, is a rare form of systemic vasculitis characterized by necrotic granulomas around the blood vessels. We report a case of a healthy 43‐year‐old man presented with multiple ulcerated lesions in head and all over the body, that has appeared spontaneously. It was characterized by a giant deep ulceration covered by thick purulent, in size from 3 to 4 cm, deep; sub febrile temperature, and minimal pain associated. Skin biopsies results pyoderma gangrenosum (PG)‐like features: anti‐neutrophil cytoplasmic antibody (cANCA) positive. Six months later, the patient developed dispea episodes. CT scan (CT) result with multiple focal opacities. He was diagnosed with wegener granulomatosis (WG) and was treated with corticosteroids and ciclophosphamide. Skin involvement in WG is not common and lesions in the skin vary from purpura, paniculitis to ulceration. In our case, skin elements are the first manifestations. Whether these elements are Wegener manifestation or we have coexistence of PG with WG, it remains a still uncertain question to answer. There is no histopathologic pathognomic elements for both. Skin involvement in WG with PG‐like lesions have been rarely reported. In front of this type of widespread ulcerations, resistant to treatment we should be aware that one of the reasons may be a disease of autoimmune etiology such as WG.